Lepidoptera larvae (Insecta) responsible for herbivory on Vanilla spp. (Orchidaceae) in the Federal District, Brazil - Specht, Alexandre (2024)
Given its culinary importance and high market value, the cultivation of Vanilla (Orchidaceae) has been expanding annually in Brazil. As observed in many crops, the increase in cultivated areas leads to a greater incidence of insects associated with species of this genus. This study reports the herbivory of larvae from Cremna thasus (Stoll, 1780) (Papilionoidea: Riodinidae: Riodininae), Hypercompe cunigunda (Stoll, 1781) (Noctuoidea: Erebidae: Arctiinae), and Spodoptera cosmioides Walker, 1858 (Noctuoidea: Noctuidae: Noctuinae) on Vanilla bahiana Hoehne and V. planifolia Andrews in the Federal District, Brazil. A list of 19 Lepidoptera species from six families associated with Vanilla spp. worldwide is provided based on a literature review. Most (n=15) of them exhibit polyphagous larvae. Given reports of exotic larvae spreading with orchids worldwide and the discussed larval polyphagy, we address precautions that producers of Vanilla and other orchids should take to reduce the incidence of insect pests in crops, especially in areas with intensive cropping systems involving annual commodities such as maize and soybean.